Vedolizumab in Refractory Microscopic Colitis: An International Case Series. (17th October 2018) - Rivière, Pauline; Münch, Andreas; Michetti, Pierre; Chande, Nilesh; de Hertogh, Gert; Schoeters, Patrick; Ferrante, Marc; Vermeire, Séverine; Van Assche, Gert
Abstract: Background: Evidence for second-line therapy in patients with microscopic colitis [MC] failing budesonide is scarce, although anti-tumour necrosis factors [anti-TNFs], methotrexate and azathioprine have been reported to be effective in small cohort studies. Vedolizumab, a monoclonal antibody targeting α4β7-integrin, prevents homing of T-cells to the gut. We evaluated clinical remission with vedolizumab in budesonide-refractory MC patients. Methods: We solicited gastroenterologists in Europe and Canada for cases of MC treated with vedolizumab. Vedolizumab 300 mg IV was administered at weeks 0, 2 and 6, and then every 8 weeks. Clinical remission and histological remission were defined as less than three stools per day and normalization of histology, respectively, after induction treatment. Results: Eleven cases were retrieved (nine females, lymphocytic colitis [LC] n = 5, collagenous colitis [CC] n = 6). Median [interquartile range] disease duration at vedolizumab initiation was 51 [29–70] months. Nine of 11 patients had failed one immunosuppressant and ten of 11 at least one anti-TNF agent. After three infusions of vedolizumab, clinical remission was observed in 5/11 patients [two LC and three CC] of whom three remained well with maintenance therapy [median duration of 13 months]. Biopsies were obtained from 9/11 patients. Histological remission was observed in 3/4 patients with clinical remission [2/3 CC, 1/1 LC] and 0/5 patients without clinical improvement. Conclusion: In a series of highly refractory MC patients, vedolizumab induced clinical remission in 5/11 subjects, of whom 75% showed normalized histology. Larger randomized trials are needed to assess the efficacy of vedolizumab in patients with MC.